Three novel Cu6S6 cluster-based coordination compounds: synthesis, framework modulation and the sensing of small molecules and Fe3+ ions. Issue 29 (5th July 2016) - Song, Jiang-Feng; Li, Si-Zhe; Zhou, Rui-Sha; Shao, Jia; Qiu, Xiao-Min; Jia, Ying-Ying; Wang, Jun; Zhang, Xiao
Abstract : Three novel Cu6 S6 cluster-based coordination compounds all display strong red light emission and naked eye colorimetric sensing for nitrobenzene, 2-nitrotoluene and Fe 3+ ions. Abstract : Three novel Cu6 S6 cluster-based coordination compounds formulated as [CuI3(mpymt)3 ]2 (1 ), {(CuI4Br4 )[CuI6(mpymt)6 ]} n (2 ), and {(CuI6I6 )[CuI6(mpymt)6 ]} n (3 ) (Hmpymt = 4-methylpyrimidine-2-thione), have been synthesized under solvothermal conditions and characterized by elemental analysis, infrared (IR) spectroscopy, thermal gravimetric analysis, powder X-ray diffraction and single-crystal X-ray diffraction. Structural analysis reveals that compound1 shows a distorted octahedral core of six copper atoms (Cu6 S6 ) constructed from four α and two β type NC–SH parts from six mpymt − anions. Compound2 displays an interesting 3D framework constructed from Cu6 S6 and Cu4 Br4 Cu(i ) clusters simultaneously, interestingly, six mpymt − with α type NC–SH parts are involved in the formation of Cu6 S6 . Compound3 displays an infinite 1D framework constructed from Cu6 S6 and Cu6 I6 Cu(i ) clusters, notably, four α and two β type NC–SH parts are involved in the formation of the Cu6 S6 cluster, however, only mpymt − ligands containing α type NC–SH parts form the bridged Cu6 I6 cluster. The experimental results reveal that halogen ions finely modulate the structural features of compounds1–3 . The fluorescent properties of compounds1–3 in the solid state and in various solvent emulsions were investigated in detail, the results of which indicate that compounds1–3 are all highly sensitive naked eye colorimetric sensors for NB, 2-NT and Fe 3+ (NB = nitrobenzene and 2-NT = 2-nitrotoluene).